Penerapan Algoritma RC6 dan Algoritma Elias Delta Code Pada Aplikasi Pengamanan dan Kompresi Short Message Service (SMS) Berbasis Android - Fadrid Jaya Immanuel Harefa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In this study software was developed that could be useful to improve the security of messages that occur in communication via SMS. SMS is a service provided by cellular phones to its users to communicate through sending short messages at a low cost. SMS is very popular, aside from being cheap, messages sent can be received by the recipient well and quickly. With this compression and security, the SMS was successfully sent and secured with smaller bits than the previous SMS. The results of compression and security using the Elias Delta Code Algorithm and RC6 Algorithm the appearance of characters or symbols that will arrive at numbers that can only be used with Android